Paligorsquitas pura e modificadas com amino silanos como sorventes para cátions metálicos e corantes aniônicos. - Ferreira, Ulysses Vieira da Silva (2013)
Clay minerals have been used for adsorption of pollutant substances. In this work, sodium palygorskite (pali) was applied for adsorption of the RN blue, RB red and yellow reactive dyes from aqueous solutions and the modified forms with silanes 3-aminepropyltrimethoxysilane (N) and 3-propylethylenediaminetrimethoxissilane (NN) were obtained. The sample pali-N were utilized for removing Cu2+, Co2+ and Ni2+ cations and the same dyes. The experimental factors as time of contact, pH and initial concentration of the adsorbates were investigated. The solids were characterized using composition chemical analysis, X-ray diffraction, 27Al and 29Si nuclear magnetic resonance, infrared spectroscopy, nitrogen adsorption-desorption measurements, thermogravimetry, scanning electronic microscopy and C, H, N elemental analysis. The results showed that the precursor pali was pure clay mineral containing traces of quartzo. The sample was a dioctaedrical type with surface area of 118 m2 g-1 constituted of aggregates of fibers. The modified solids showed an immobilization degree of 0.92 and 0.67 mmol g-1 for pali-N and pali-NN, respectively. The results of dye adsorption on pure sample showed the maximum retention of 55 mg g-1 for reactive blue RN and red RB and 45 mg g-1 for reactive yellow GR. For sample pali-N, the maximum adsorption capacities were 120, 110 and 100 mg g-1 for red RB, blue RN and yellow GR, respectively, which all processes were described by pseudo- second-order kinetic and the equilibrium data were fitted to Langmuir model. In the adsorption of metal cation on pali-N, the maximum adsorbed quantities were 0.73, 0.62 and 0.58 mmol g-1 for Cu2+, Co2+ and Ni2+, respectively. The data were fitted to pseudo-second-order kinetic and the equilibrium data were fitted to Langmuir model.